Cyber-Physical System and Curriculum Heutagogy Implementation in Higher Education for Creating 4.0 Generation - Prasetyono, Hendro; Ramdayana, Ira Pratiwi; Desnaranti, Laila (IJECA (International Journal of Education and Curriculum Application), 2022)
Higher education management must change its management model because the student's current needs in the Industrial Revolution 4.0 era are very diverse and the demand from the industrial world is more specific. This situation required a new approach in learning that can meet the students learning needs, therefore, can generate higher education graduates that have the capability, not competencies. This article is compiled based on the results of thoughts supported by a literature review using content analysis based on the results obtained from 58 articles that were published between 1999 and 2020. The universities can implement heutagogy in the curriculum which is supported by the cyber-physical system in learning. This is causing the students to be able to choose scientific competence they want independently with learning across disciplines for occupying certain ability. The cyber system development in higher education is used to assist the online learning process and as an administrator in supporting learning activities. The cyber-physical system refers to the physical things and the campus atmosphere felt by the students.